REVISITING A STUDY OF AWARENESS AND PERCEPTION TOWARDS SUSTAINABILITY - Naziatul Aziah Mohd Radzi; Normaizatul Akma Saidi; Hasif Rafidee Hasbollah; Hazzyati Hashim; Fadhilahanim Aryani Abdullah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Sustainability has long been discussed in many perspectives considering its importance to our lives. The practices embedded in Sustainability must consistently be done to achieve the goals that have been set in the Sustainability Development Goals (SDG) especially to fight a climate change and to create the sustainable cities and communities. To practise sustainability successfully, people should be aware and have a better understanding of sustainability issues and practices. Thus, this paper intends to look at the trends and issues in the awareness and perception towards sustainability. A conceptual paper in nature, this study reviewed past research works which included the perception and awareness of sustainability. This paper gathered study patterns and accessed the findings from multiple previous studies. Based on the findings, the awareness of sustainability was found to sustainability principles among the society. Education is recognised to have played a significant role of increasing the awareness of sustainability. Hopefully, this study will shed a light on the perspective of awareness and the perception towards sustainability from many different angles, which perhaps could lead to a new direction of study on this topic.